Analysis of Regional Property Procurement based on Presidential Regulation no. 12 of 2021 to the Manado City Government - Faiji Tampilang; Jantje Tinangon; Lidia Mawikere (Formosa Journal of Applied Sciences, 2023)
This research aims to analyze whether the procedures for procurement of regional property (BMD) in the Manado City government are in accordance with Presidential Regulation no. 12 of 2021 or not. The research method used is qualitative methods, with data collection methods through interviews and documentation. The results of this research show that in the Manado City Government at BKAD the author analyzes the procedures for procurement of Regional Property Goods in accordance with applicable regulations from the process of the Technical Commitment Making Officer for Activities who makes a letter of application to the Budget User until the goods are received by the PPK from the goods administrator after signing the Minutes Handover (BAST).